Exchange Structures Between English Lecturer and Health Information Management Students in English Class at Deli Husada Deli Tua Health Institute - Herawati Br Bukit (BEST Journal (Biology Education, Sains and Technology), 2021)
The study reasons were to know what exchanges structures used between English Lecturer and Health Information Management (HIM) students and to obtain development of English learning strategies for health students. This research is conducted by descriptive qualitative. The data were clauses produced by English lecturer and HIM students. The data is analyzed based on Martin theory. In conversation, lecturer tends to has initiative to start it, meanwhile, the students tend to give respond by doing activity (evade) which are instructed by the lecturer. It is found 13 types corresponding moves of information, goods and services exchanges. The dominant exchanges structure were k2^k1 and a1^a2f^a1f. It is found different case, when lecturer gave the information to student that is marked by k1, it is followed by k1 or signed by k2^k1(k2)^k1(k2)^k1. There were two conversational systems namely congruent and metaphorical coding. In conversational structures, as the realizations of conversational systems, it is found some marked structures. Students didn’t answer the question, because undeniable that health students have difficult ability for making dialogue in English therefore lecturer keeps the conversation going by undergone initiative actions such as giving information, asking question or giving instruction but s/he seems to repeat information